Tuberous Sclerosis Complex Associated Lymphangioleiomyomatosis Presenting with Spontaneous Pneumothorax and Renal Angiomyolipomas (Bangladesh Medical Journal, 2019)
Tuberous sclerosis complex (TSC) is a rare autosomal dominant disorder manifested by involvement of multisystem including skin, central nervous system, heart, kidneys and eyes. Lymphangioleiomyomatosis (LAM) is also a multisystem disorder that primarily affects the lungs. We report a case of tuberous sclerosis complex associated lymphangio-leiomyomatosis (TSC-LAM) in a 26-year-old female patient who was presented with spontaneous pneumothorax and renal angiomyolipomas. In clinical examination; We found multiple angiofibromas over her face, shagreen patches over upper and lower back and ungual fibromas in both fingers and toes. HRCT of chest revealed right sided pneumothorax with multiple thin walled cysts in both lungs. Ultrasonogram (USG) and Computer Tomography (CT) scan of abdomen revealed bilateral angiomyolipomas. We managed her pneumothorax with intercostal chest tube drainage and oxygen inhalation.Bangladesh Med J. 2019 May; 48 (2): 51-54